View of Roslyn Chapel, at the Diorama - Daguerre, Louis Jacques Mandé, 1787-1851 (Victorian popular culture. Moving pictures, optical entertainments and the advent of cinema., 2012)
View of the chapel at Rosslyn Castle, near Edinburgh, by Daguerre, as exhibited at his London Diorama in Regent's Park.